Effect of combined exercise training and behaviour change counselling versus usual care on physical activity in patients awaiting hip and knee arthroplasty: A randomised controlled trial. Issue 4 (December 2022) - Williams, Andrew D.; O'Brien, Jane; Mulford, Jonathan; Mathew, Ronnie; Thapa, Deependra Kaji; Hamilton, Kyra; Cheney, Michael; Schmidt, Matthew; Wu, Sam; Bird, Marie-Louise
Abstract: Objective: This study aimed to determine if a novel intervention that combined individualised exercise training with behaviour change counselling based on Health Action Process Approach (HAPA) constructs could elicit long-term increase in physical activity (PA) and reduce comorbidity development among people requiring hip or knee arthroplasty. Method: A pre-registered two arm, parallel group, randomised controlled trial comparing the effect of a 12-week individualised exercise program combined with behavioural counselling delivered by accredited exercise physiologists, versus usual care to Osteoarthritis (OA) patients on public surgery waitlists. Participants were followed up at 6 months after baseline (pre-surgery) and again at 6 months post-surgery. Within and between group differences in post-surgery PA (as measured by ActivPal accelerometer), pain, function, quality of life, HAPA-based behavioural and psychological constructs, and health risk factors were analysed. Results: 63 participants (34 Female; Mean age ​= ​66.4 ​± ​7.2 ​yrs) consented to participate in this study. At 6 months post baseline and 6 months post-surgery there were significant improvements in PA, pain, function, and quality of life, however there were no significant differences in the between group responses. Significant between group changes were observed in several psychological constructs related to volition at 6 months post baseline; however, these had disappeared by 6 months post-surgery. Conclusions: An exercise program and HAPA guided counselling intervention can improve psychological constructs related to exercise behaviour; however, these did not result in significant between group changes in PA at the timepoints measured. Further research with larger sample size is required. Trial Registration: Australian New Zealand Clinical Trials Registry (ACTRN 12617000357358) Date of registration: 08/03/2017.